Profiling of Biomarkers for the Exposure of Polycyclic Aromatic Hydrocarbons: Lamin-A/C Isoform 3, Poly[ADP-ribose] Polymerase 1, and Mitochondria Copy Number Are Identified as Universal Biomarkers. (8th July 2014) - Kim, Hwan-Young; Kim, Hye-Ran; Kang, Min-Gu; Trang, Nguyen Thi Dai; Baek, Hee-Jo; Moon, Jae-Dong; Shin, Jong-Hee; Suh, Soon-Pal; Ryang, Dong-Wook; Kook, Hoon; Shin, Myung-Geun
Abstract : This study investigated the profiling of polycyclic aromatic hydrocarbon- (PAH-) induced genotoxicity in cell lines and zebrafish. Each type of cells displayed different proportionality of apoptosis. Mitochondrial DNA (mtDNA) copy number was dramatically elevated after 5-day treatment of fluoranthene and pyrene. The notable deregulated proteins for PAHs exposure were displayed as follows: lamin-A/C isoform 3 and annexin A1 for benzopyrene; lamin-A/C isoform 3 and DNA topoisomerase 2-alpha for pentacene; poly[ADP-ribose] polymerase 1 (PARP-1) for fluoranthene; and talin-1 and DNA topoisomerase 2-alpha for pyrene. Among them, lamin-A/C isoform 3 and PARP-1 were further confirmed using mRNA and protein expression study. Obvious morphological abnormalities including curved backbone and cardiomegaly in zebrafish were observed in the 54 hpf with more than 400 nM of benzopyrene. In conclusion, the change of mitochondrial genome (increased mtDNA copy number) was closely associated with PAH exposure in cell lines and mesenchymal stem cells. Lamin-A/C isoform 3, talin-1, and annexin A1 were identified as universal biomarkers for PAHs exposure. Zebrafish, specifically at embryo stage, showed suitable in vivo model for monitoring PAHs exposure to hematopoietic tissue and other organs.